Cerebrospinal fluid biomarkers and cognitive status in differential diagnosis of frontotemporal dementia and Alzheimer's disease. Issue 10 (October 2019) - Casoli, Tiziana; Paolini, Susy; Fabbietti, Paolo; Fattoretti, Patrizia; Paciaroni, Lucia; Fabi, Katia; Gobbi, Beatrice; Galeazzi, Roberta; Rossi, Roberto; Lattanzio, Fabrizia; Pelliccioni, Giuseppe
Objective: This study aimed to determine the most appropriate cognitive and cerebrospinal fluid (CSF) biomarker setting to distinguish frontotemporal dementia (FTD) from Alzheimer's disease (AD). Method: Patients with FTD, those with AD, and those without dementia were enrolled in this study. CSF amyloid-ß 42 (Aß42), total (t)-tau, and phosphorylated (p)-tau concentrations were determined by enzyme-linked immunosorbent assays. Cognition was evaluated by the Mini-Mental State Examination (MMSE) and its domain scores. The associations of CSF biomarkers with cognitive measures were examined using regression models and the diagnostic value of CSF biomarkers was determined by receiver operating characteristics curves. Results: CSF Aß42 levels were lower, whereas t-tau/Aß42 and p-tau/Aß42 ratios were higher in patients with AD compared with those with FTD. Some MMSE domain scores were different in FTD and AD, but they did not improve the ability to distinguish between the two pathologies. Poor temporal orientation scores were associated with low Aß42 levels only in patients with FTD. The p-tau/Aß42 ratio reached sufficient levels of sensitivity and specificity to discriminate FTD with primary progressive aphasia from AD. Conclusions: The ratio of CSF p-tau/Aß42 is a sensitive and specific biomarker for discriminating patients with primary progressive aphasia from those with AD.